Societal acceptance of an emerging energy technology: How is geothermal energy portrayed in Australian media?. (February 2015) - Romanach, Lygia; Carr-Cornish, Simone; Muriuki, Grace
Abstract: The media shapes and is shaped by public sentiment of emerging technologies. One way to gauge the societal acceptance levels of an emerging technology, such as geothermal energy technology in Australia, is to analyse how the technology is reported in the media. This study identified the benefits and risks that have been reported and the social actors represented, informed by extant research of factors that impact societal acceptance. A total of 451 Australian news items on geothermal energy technology published between July 1st, 2011 and June 30th, 2012 were used for this content analysis, which encompassed the release of the Australian Government׳s Clean Energy Plan . Consistent with geothermal technology being an emerging technology in Australia, economic feasibility and uncertainty about the technology were the most frequently reported risks. Industry was one of the most cited social actors in geothermal news media and it was more likely to be cited in articles reporting the economic feasibility and uncertainty about the technology, reflecting the current state of the industry in Australia. Renewable and low-emission energy were the most frequently cited benefits, which were often reported as part of the Australian Government Clean Energy Plan . Overall, this emerging technology has maintained a restricted profile in the media to date, with limited controversy or politicisation. This profile is likely to remain, in particular the focus on the technology economic feasibility, which remains the main challenge to the technology entering large-scale development in Australia.